Reconstructing Justice: The Evolution and Application of International Humanitarian Law in Post-Assad Syria - Zreik, Mohamad; Caba-Maria, Flavius (Faculty of Law, Universitas Brawijaya, 2025)
The Syrian Civil War, spanning over a decade, has been marked by severe violations of International Humanitarian Law (IHL), including indiscriminate attacks on civilians, torture, and the use of chemical weapons. Despite the ousting of President Bashar al-Assad in December 2024, the conflict persists, with new actors and shifting alliances complicating the enforcement of IHL. This paper examines the evolution of IHL in Syria, analyzing key case studies such as the Siege of Eastern Ghouta, the 2025 massacres of Alawites, and the establishment of transitional justice mechanisms. Utilizing a case study methodology, the paper assesses the effectiveness of IHL in mitigating humanitarian crises and explores the challenges and prospects for accountability and reform in the post-Assad era.